Plyometric training effects on athletic performance in youth soccer athletes: A systematic review - Bedoya, A. A.; Miltenberger, M. R.; Lopez, R. M. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this systematic review was to critically analyze the literature to determine the effectiveness of plyometric training on athletic performance in youth soccer athletes. A total of 7 studies were included in this review after meeting the following criteria: (a) used plyometric training programs to assess athletic performance, (b) subjects were soccer athletes aged preadolescent up to 17 years, and (c) were published from 2000 to January 2014. Study methods were assessed using the PEDro scale with scores ranging from 4 to 6. Results showed similarities and differences in methodologies and procedures among the included studies. Athletic performance consisting of kicking distance, speed, jumping ability, and agility significantly improved because of plyometric training interventions. The current evidence suggests that plyometric training should be completed 2 days per week for 8-10 weeks during soccer practice with a 72-hour rest period between plyometric training days. The initial number of foot contacts should be 50-60 per session and increase to no more than 80-120 foot contacts per session for this age group to prevent overuse injuries. A total of 3-4 plyometric training exercises should be performed 2-4 sets for 6-15 repetitions per training session. The evidence and the literature suggest that plyometric training for this age group should only be implemented using recommended safety guidelines such as those published by the Canadian Society for Exercise Physiology and the National Strength and Conditioning Association and under appropriate supervision by trained personnel.